Student Assessment of the Personality Competence and Social Competence of Islamic Religious Education Teachers - Yaumas, Nova Erlina; Yemmardotillah, M.; Sari, Mukhtia; Nisa, Fadhila Khairatun; Mulyawati, Husni; Nasir, Ainul Athirah Binti Abdull (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
Personality and social competencies are two out of four competencies that should be possessed by those who teach Islam education. The two competencies are not merely observed and assessed when teachers are in classe or school environment, but also in their domicile surroundings. The study is aimed at analyzing learners’ assessment on their teachers’ personality and social competencies. The study employs quantitative method through survey approach. Data are collected by likert scale questionnaires of fifteen questions related to the competencies which spreaded to three hundred eighty-two students of distinctive High Schools in Indonesia. The respondents are selected through the method of total random sampling. All data are descriptively analyzed by a software of SPSS version 26. The findings of the study reveal that the personality and social competencies of Islamic religious education teachers are satisfactory. Thus, the findings object the prior studies that shows the two competencies of islamic religious education teachers are low. Finally, the findings can be an initial idea for more advanced study related to teachers’ competencies in different contexts and levels.